The use of continuous monitoring blood culture systems in the diagnosis of catheter related sepsis. - Rogers, M S (1998)
AIM: To assess whether the information provided by automated continuous monitoring blood culture systems could aid in the diagnosis of catheter related sepsis. METHODS: Serial dilutions of a strain of coagulase negative staphylococcus were inoculated into the BacT/Alert blood culture system. Blood culture results for seven patients with possible catheter related sepsis from coagulase negative staphylococci were reviewed. RESULTS: Time to positivity and length of lag period were strongly related to the concentration of bacteria inoculated (average decrease of 1.5 hours to positivity for each 10-fold increase in concentration). Time to positivity and length of lag period were significantly shorter for central line blood cultures than for those taken from peripheral sites. CONCLUSIONS: Using data already measured by continuous monitoring blood culture systems may provide a simple alternative to quantitative blood cultures for the diagnosis of catheter related sepsis.